2020
DOI: 10.3390/ani10081298
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Parenteral Supplementation with Minerals and Vitamins on Oxidative Stress and Humoral Immune Response of Weaning Calves

Abstract: We aimed to evaluate the effects of injectable mineral and vitamin supplementation on weaning calves subjected to a low-stress (fence-line) weaning system. Seven-month-old Aberdeen Angus female calves (n = 40, 152 ± 11 kg body weight) from a selenium-deficient area of extensive cattle production on natural grass were randomly assigned to two groups (n = 20 each). One group received subcutaneous supplementation with copper, zinc, selenium, manganese and vitamins A and E (SG), and the other was given sterile sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 52 publications
0
18
0
1
Order By: Relevance
“…Although plasma TAS has been effective in evaluating the antioxidant capacity in dairy cows ( Castillo et al, 2006 ; Gong and Xiao, 2016 ), in trials with calf transport plasma TAS response has been inconsistent. In a trial in calves that received similar supplementation to the one evaluated in the current experiment, weaned on pasture with a fence-line system and without subsequent transport, plasma TAS was greater in supplemented calves compared with nonsupplemented calves ( Mattioli et al, 2020 ). On the other hand, Chirase et al (2004) observed that plasma TAS decreased by only 10% in weaned and transported calves for 1,930 km and 20 h in transit.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Although plasma TAS has been effective in evaluating the antioxidant capacity in dairy cows ( Castillo et al, 2006 ; Gong and Xiao, 2016 ), in trials with calf transport plasma TAS response has been inconsistent. In a trial in calves that received similar supplementation to the one evaluated in the current experiment, weaned on pasture with a fence-line system and without subsequent transport, plasma TAS was greater in supplemented calves compared with nonsupplemented calves ( Mattioli et al, 2020 ). On the other hand, Chirase et al (2004) observed that plasma TAS decreased by only 10% in weaned and transported calves for 1,930 km and 20 h in transit.…”
Section: Discussionmentioning
confidence: 84%
“…The steers were randomly assigned to four treatments: 1) MVS+PC, steers with MVS and preconditioned, n = 15; 2) N+PC, steers with no MVS and preconditioned, n = 15; 3) MVS+N, steers with MVS and not preconditioned, n = 15; and 4) N+N, steers with no MVS and preconditioned, n = 15. The number of animals was selected based on a power analysis, using results from a previous research with the use of a similar MVS ( Mattioli et al, 2020 ). The mineral and vitamin treatment was applied subcutaneously (s.c.) at a dose of 1 mL/50 kg of BW.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated ROS production compromises genomic stability and disrupts protein and lipid structures (Koch and Hill, 2017), overwhelming cellular antioxidant defense system (Burton and Jauniaux, 2011). Supplemental antioxidants delay or inhibit oxidation of the oxidizable substrates (Betteridge, 2000) that play an important role for the immune defense and health of stressed cattle (McDowell, 2000;Mattioli et al, 2020). Antioxidants such as Vitamin E and β-carotene are considered chain-breaking antioxidant (Betteridge, 2000;McDowell, 2000;Baj et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidants such as Vitamin E and β-carotene are considered chain-breaking antioxidant (Betteridge, 2000;McDowell, 2000;Baj et al, 2019). Accordingly, these two vitamins are routinely supplemented in receiving diets to counteract pro-oxidant status, promoting both health and growth performance (Alosilla Jr et al, 2007;Abuelo et al, 2015;Mattioli et al, 2020). In vivo and in vitro Vitamin A and E evaluations indicate a greater efficiency of utilization when supplemented parenterally rather than orally (Rode et al, 1990;McDowell, 2000;Snider et al, 2014).…”
Section: Introductionmentioning
confidence: 99%